SAFETY AT THE WORKPLACE: ACADEMICS’ AWARENESS AT HIGHER EDUCATION INSTITUTIONS IN MELAKA - Nor Hasliza Mat Hasan; Nor Fauziana Ibrahim (Malaysian Journal of Public Health Medicine, 2023)
The research was carried out to assess the academics’ awareness of occupational safety and health (OSH) at higher education institutions in Melaka. Questionnaires were the primary data collection tools used in this study. The cross-sectional design was used in this research. The survey was distributed to 200 respondents, and 151 valid responses were received from the higher education institutions in Melaka. The collected data were analysed using a structural equation modelling by partial least squares executed by the SMART-PLS software. The results showed that safety tools and equipment, safety policy, and safety procedures have a significant positive relationship with academics’ awareness at higher education institutions (p<0.05). However, safety training does not affect academics’ awareness of OSH at the workplace (p>0.05). This study enhances the OSH implementation strategies to ensure the safety of academics in the workplace. Hence, it will contribute to the development of a positive safety culture in the workplace.